Las tecnologías de información y comunicación (TIC) en el aprendizaje de la Asignatura de Anatomía de la Carrera de Medicina Humana de la Universidad Nacional de Loja - Calva Ochoa, Karen Jackeline (2024)
The use of Information and Communication Technologies (ICT) in the educational field, especially in fields such as health, has grown exponentially, enriching the teaching of subjects such as Human Anatomy, Pharmacology, and Human Histology. ICTs function as teaching aids, enhancing students' creativity, abilities, and skills. Although they do not replace practical instruction in the amphitheater, they complement them. The objective of this study is to analyze the use of technological tools in the teaching-learning process of Human Anatomy in students of the Human Medicine program at the National University of Loja. The methodology adopted a mixed approach; in addition, a non-experimental correlational scope that includes the application of a questionnaire to students of the fifth cycle and the rotating internship. The results highlight the type of ICT used by students to improve their teaching-learning process, the most commonly used being Augmented Reality (virtual Anatomy table) with 34%, Simulators with 29%, Software programs (web applications) with 19%, as well as 3D models with 14% and finally digital books with a minimum percentage of 4%. It is important to mention that students use more than one technological tool. In conclusion, the integration of ICT within the curriculum contributes greatly to the learning process, allowing interaction with the teacher; which will help the student to acquire and develop skills to achieve meaningful learning that allows relating practice with the clinic. Keywords: ICT; teaching - learning; Human Anatomy; learning styles, augmented and virtual reality.